Development of Khoa-Mak Beverages from Low Grade Riceberry Rice and Low Grade Brown Rice in Chachoengsao Province - Srisuk, Narakorn (YRU Journal of Science and Technology, 2022)
The objective of this research was to utilize the broken rice, agricultural by-product in which more obtained at Chachoengsao, for development of the new Khoa-Mak beverages. The study included broken glutinous rice and broken riceberry Rice at the ratios of 100:0, 0:100, 50:50, 70:30 and 90:10 w/w and broken glutinous rice and broken brown rice at the ratios of 100:0, 0:100, 50:50, 70:30 and 90:10 w/w in order to analyze their sensory qualities and overall acceptance as well as to study the biological activity of Khoa-Mak beverages in various formulations including antioxidant activity, phenolic content, anthocyanin content, and physical-chemical qualities. The results showed that Khoa-Mak beverages prepared from broken glutinous rice and broken riceberry Rice at the ratios of 70:30 and 90:10 w/w obtained highest overall acceptability score (P>0.05) of 7.47 and 7.46, respectively. In addition, Khoa-Mak beverages prepared from broken glutinous rice and broken riceberry rice at the ratios of 70:30 w/w showed the highest yields of antioxidant activity of 42.58%, total phenolic acid of 220.73 mg GAE/g and anthocyanin of 245.56 mg/l. They also received an overall acceptability of “moderately like” on the scale used. Therefore, broken glutinous rice and broken riceberry rice at the ratio of 70:30 w/w were selected to produce the Khoa-Mak beverages used to check the quality according to standard TCPS No. 162/2546. The microbiological quality test results showed no pathogens at the Khoa-Mak beverages and complied with product standard TCPS No. 162/2546.